Empowerment and Reproductive Women: An Exploratory Research - Tarikere, Pradeep S; Vidya G S; Krishnaveni Y S (National Journal of Community Medicine, 2018)
Background: Women play an important role in welfare of family. High fertility continues in India adversely affecting poorer women, with no empowerment regarding temporary and perma- nent methods in family planning and also poor decision taking due to lack of freedom in day to day activities. So assessment of empowerment among women explores hurdles to family planning programme and resolving them. Methodology: An exploratory study done among rural population by interviewing 150 antenatal women, 40 men and conducting fo- cus grouped discussion(FGD) in postnatal women using pur- posive sampling and quota samplings respectively. Information on decision making regarding personal, household, and social issues collected and analyzed and summarized. Results: Majority of the women are home makers, 47.2% belonged to age 21 to 25 years. Though 50% took decision regarding their education and 59.7% on voting by themselves, other issues like choosing life partners, household purchases, children’s education and income generation were decisions taken from other family members with male domination. Women’s ‘decision making’ in reproductive and contraceptive issues were limited and confined to egalitarian. Misconceptions regarding sterilization procedures were obvious in FGD. Conclusion: Women still lack freedom in decision making in their personal, household and reproductive issues, revealing gaps which needs to be addressed in term of women empowerment.